Polyphasic characterization of Aspergillus section Flavi isolated from animal feeds in Algeria - Bouti, Karima; Verheecke-Vaessen, Carol; Mokrane, Salim; Meklat, Atika; Djemouai, Nadjette; Sabaou, Nasserdine; Mathieu, Florence; Riba, Amar (Wiley, 2019)
In Algeria, little information is available on the population structure of Aspergillus section Flavi in raw materials and resultant animal feeds. A total of 172 isolates belonging to Aspergillus section Flavi were recovered from 57 animal feeds and identified on the basis of macro and micro‐morphological characters, mycotoxin production and genetic relatedness. For the molecular analysis, sequencing of the calmodulin gene (CaM) and the internal transcribed spacer (ITS) regions were performed for representative isolates. Four distinct morphotypes were distinguished: Aspergillus flavus (78.5%), Aspergillus tamarii (19.2%), Aspergillus parasiticus (1.7%), and Aspergillus alliaceus (0.6%). All A. flavus isolates were of the L type and no correlation between sclerotia production and aflatoxigenicity was observed. Our results showed that 68% of the A. flavus strains produced aflatoxins B (AFB), and 72.7% were cyclopiazonic acid (CPA) producers. The three isolates of A. parasiticus were able to produce AFB and aflatoxins G but not CPA whereas, all the strains of A. tamarii produced only CPA. The obtained results revealed the presence of different species of Aspergillus section Flavi, among which were aflatoxin producers. This study provides evidence useful for considerations in aflatoxin control strategies.
Keywords: Aspergillus section Flavi; Polyphasic identification; Animal feeds; Aflatoxins; Algeria